Atherogenic index of Plasma and LDL/HDL ratio in Patients with Chronic Obstructive Pulmonary Disorder with Special Reference to Risk of Cardiovascular Diseases - Khan, Tooba (International Journal of Pathology, 2023)
Background: The atherogenic index of plasma (AIP) and LDL/HDL ratio was considered as a strong predictor in the development of cardiovascular diseases (CVDs) particularly in patients with chronic obstructive pulmonary disease (COPD). The present study aimed to determine the AIP and LDL/HDL ratio in patient with COPD and to find out the risk of CVDs in these patients. Materials and Methods: This single centered cross-sectional study was conducted in the department of pulmonology, Khyber Teaching Hospital Peshawar. 150 COPD patients were enrolled in the study according to the GOLD guidelines. After proper consent, 5cc fasting blood samples were withdrawn from all patients for biochemical analysis. Body mass index (BMI), atherogenic index of plasma (AIP) and LDL/HDL ratio were calculated as per protocols previously described. All the data was entered in SPSS version 22.0. Independent sample t-test was applied to established association between dyslipidemia, AIP and LDL/HDL ratio. Pearson correlation was applied to determine any correlation between study variables. Results: Mean age was 57.34 ± 9.6 years. Out of 150 COPD patients, 62 (41.3%) were females while 88 (58.7%) were males. Strong association between dyslipidemia and AIP and dyslipidemia and LD/HDL ratio with p-value <0.001 was observed. Strong positive correlation was onserved between BMI and total cholesterol (TC) (r=0.31), triglycerides (TGs) (r=0.52), low density lipoprotein (LDL) (r=0.26), very low density lipoprotein (VLDL) (r=0.52), AIP (r=0.4) and LDL/HDL ratio (r=0.27) where as strong negative correlation with disease duration (r=-0.24) and weakly correlated with high density lipoprotein (HDL) level (r=0.04). Furthermore, TC showed strong positive correlation with TGs (r=0.32), HDL (r=0.35), LDL (r=0.91), VLDL (r=0.32) and LDL/HDL ratio (r=0.58). There was a strong positive correlation observed in AIP and BMI (r=0.4), TGs (r=0.81), VLDL (r=0.81) and HDL (r=0.60). The LDL/HDL ratio was also strongly positive correlated with BMI (r=0.27), TC (r=0.58), TGs (r=0.27), LDL (r=0.77), VLDL (r=0.27) and AIP (r=0.48) while strongly negative correlated with age (r= -0.2) and HDL (r= -0.46). Conclusion: In our study, COPD patients are at higher risk of developing CVDs.